Microsphere filler and application thereof

By combining self-assembled polypeptides and microspheres, a nano-scale three-dimensional network structure is formed, which solves the problem of uneven dispersion of microsphere fillers during redissolution, achieves uniform dispersion and support, simplifies the production process and reduces costs.

CN119548672APending Publication Date: 2025-03-04CYTOPORT (TIANJIN) BIOTECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411573394.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing microsphere fillers are difficult to disperse evenly during redissolution, resulting in side effects such as difficulty in injection and inflammation. Chemical modification of microspheres will increase production costs and there is a problem that crosslinking agents cannot be safely removed.

Method used

Self-assembled polypeptide compounds are combined with microspheres, and a nanoscale three-dimensional network structure is formed through self-assembly to support the uniform dispersion and stereoscopic distribution of microspheres, avoiding chemical modification of microspheres.

Benefits of technology

The uniform dispersion and support of microspheres is achieved, the production process is simplified, the cost is reduced, the side effects are avoided, and the long-term beauty effect is achieved in the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548672A_ABST
    Figure CN119548672A_ABST
Patent Text Reader

Abstract

The invention discloses a microsphere filler, and belongs to the field of biological medicine, the filler comprises polypeptide and microspheres capable of forming a net-shaped support, self-assembled peptide molecules in the preparation form a complex with a net-shaped structure in an aqueous solution, the dispersion and support effects can be achieved without modifying the microspheres, and the self-assembled peptide molecules in the preparation can be used for preparing the microsphere filler. And the problem of difficult injection due to microsphere aggregation is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to the field of biomedical materials, and in particular to a composition of self-assembling peptides and medical aesthetic microspheres. Background technology:

[0002] Degradable microspheres have been widely used in biomedicine as regenerative filling ingredients in recent years. Medical microspheres such as poly(L-lactic acid) stimulate fibroblasts to produce new collagen and other connective tissue collagen, rejuvenate cells, promote skin tissue regeneration and repair, increase skin elasticity and firmness, and thus achieve comprehensive improvement of skin condition and anti-aging. At the same time, degradable components such as poly(L-lactic acid) enter the skin and are gradually degraded into lactic acid, which is eventually metabolized into carbon dioxide and water by the human body. It is a natural organic matter that is harmless to the human body.

[0003] At present, many microsphere fillers on the market have problems of uneven microsphere adhesion and dispersion and difficulty in injection during re-dissolution, which easily leads to side effects such as inflammation after injection. However, the microsphere filler is chemically modified. For example, the patent with patent document number CN202311619276.3 discloses a method using gelatin and hyaluronic acid as a thickener and dispersant. By adding a thickener to improve the dispersibility of the microspheres, on the one hand, the production cost is increased, and on the other hand, there is also the problem that the cross-linking agent cannot be safely removed. If too much, large molecular hyaluronic acid is injected, and the doctor's skills are insufficient, it will cause unexpected situations such as agglomeration, allergies, and facial stiffness.

[0004] Self-assembling peptides are nanoscale three-dimensional network structures formed by self-assembly of polypeptide molecules through non-covalent bonding forces. The gel and fiber network formed are conducive to the full diffusion of nutrients and provide a nanoscale microenvironment for cell adhesion and growth. Therefore, self-assembling peptides provide support for L-polylactic acid microspheres while promoting cell proliferation and differentiation.

[0005] Therefore, it is urgent to develop a technical method that can exert the supporting and repairing functions of microsphere fillers without chemically modifying the microspheres and without introducing exogenous substances. Summary of the invention:

[0006] The purpose of the present invention is to chemically modify the microspheres and various fillers in view of the fact that the existing microsphere fillers are difficult to disperse uniformly during re-dissolution, and to provide a self-assembling peptide microsphere system that can play a dispersing and supporting role without modifying the microspheres, which can be applied to biomedicine fields such as drug delivery and wound healing.

[0007] The first aspect of the present invention provides a microsphere filler, comprising a self-assembling polypeptide compound and microspheres; the polypeptide compound can form nano-scale fibers in a solution without chemical modification and present a three-dimensional network structure; and the three-dimensional network structure can support the microspheres in the solution so that they are evenly dispersed and three-dimensionally distributed.

[0008] The self-assembling peptide of the present invention realizes the self-assembly of polypeptide molecules through weak interactions such as hydrophobic interaction, ionic bond, van der Waals force and hydrogen bond, and finally forms a nano three-dimensional network structure. The three-dimensional network structure is automatically repaired by non-covalent bond force, and the medical beauty microspheres are fixed in the network structure, and the uniform dispersion effect of the medical beauty microspheres in the self-assembling peptide solution is maintained. Therefore, after adding the medical beauty microspheres, the medical beauty microspheres can be evenly dispersed in the self-assembling peptide solution after slight shaking, and the finished product of the medical beauty microsphere filler can be simply obtained. In addition, the self-assembling peptide can support the microspheres under liquid conditions. At the same time, since the system can be directly activated to become a gel after entering the human body, the immediate beauty effect of the polypeptide is achieved, and the microspheres can achieve a long-lasting beauty effect. The long-term and short-term beauty effects are combined through the self-assembly behavior of the polypeptide.

[0009] In a specific embodiment, in the microsphere filler, the polypeptide compound is selected from the following polypeptides:

[0010] SEQ ID 1, IIIIIGSIIGPGGEGPGGV

[0011] SEQ ID 2, FLIVIGSIIGPGGDGPGGV

[0012] SEQ ID 3, FLIVIGSIIGPGGEGPGGV

[0013] SEQ ID 4, FLIVIGSIIGPGGDGPGGD

[0014] SEQ ID 5, GIIIG

[0015] SEQ ID 6, GIWLG.

[0016] In a specific embodiment, in the microsphere filler, the microspheres are not chemically modified; preferably, the microspheres are selected from at least one of L-polylactic acid microspheres, polycaprolactone microspheres, polylactic acid-glycolic acid microspheres, hydroxyapatite microspheres, polymethyl methacrylate microspheres and polyvinyl alcohol microspheres.

[0017] Preferably, the particle size of the microspheres is 3-150 μm;

[0018] Different microspheres have their optimal particle sizes. Preferably, the particle size of polylactic acid microspheres is 10-60 μm, the particle size of polycaprolactone microspheres is 10-60 μm, the particle size of polylactic acid-glycolic acid microspheres is 20-60 μm, the particle size of hydroxyapatite microspheres is 25-45 μm, and the particle size of polymethyl methacrylate microspheres is 20-60 μm.

[0019] The second aspect of the present invention provides a preparation of the aforementioned microsphere filler, wherein the preparation is a solution preparation, a lyophilized powder preparation, or a suspension preparation.

[0020] In a specific embodiment, the solution in the solution preparation or suspension is water, or physiological saline, or phosphate buffer.

[0021] When the solution preparation or freeze-dried powder preparation is used, the concentration of microspheres is controlled at 10wt%-40wt%; the concentration of the polypeptide is controlled at 0.05%-2%.

[0022] The third aspect of the present invention provides the use of a microsphere filler or a microsphere-filled preparation, wherein the microsphere filler or microsphere-filled auxiliary agent is used in regenerative medicine and tissue regeneration; drug delivery; wound healing; implantable materials; gene therapy; stem cell therapy; and medical cosmetology.

[0023] The present invention provides a polypeptide fast-redissolving microsphere filler. The self-assembling peptide molecules in the preparation form a complex in an aqueous solution, which plays a role in dispersing and supporting the medical beauty microspheres. At the same time, after the solution of the preparation is injected into the tissue, it can play a tissue support function, thereby achieving an immediate beauty effect.

[0024] When using the microsphere filler or microsphere-filled preparation, first add injection water, physiological saline or phosphate buffer solution to the freeze-dried polypeptide powder and mix them evenly. The dissolved polypeptide self-assembles to form a three-dimensional network structure under the action of non-covalent bonds. The network structure formed by the self-assembled polypeptide supports the medical beauty microspheres in a liquid state, so that the medical beauty microspheres are evenly three-dimensionally distributed in the polypeptide self-assembled network material, and a uniformly dispersed medical beauty microsphere filler that can be injected and filled can be quickly obtained.

[0025] The self-assembling peptide solution in the preparation of the present invention not only has the advantage of quickly assembling to form a hydrogel in a short period of time, but also has the characteristics of shear thinning and rapid recovery to the original state after the external force is removed. This shows that under the action of strong external mechanical force, some non-covalent bonds inside the self-assembling peptide hydrogel will break, and the macroscopic manifestation is that the gel state is destroyed and becomes a solution; when this mechanical force disappears, these broken non-covalent bonds will reconnect, and the macroscopic manifestation is that the destroyed gel recovers to a state close to the original gel through self-repair. And the recovery time of the hydrogel does not exceed 10 minutes, and the storage modulus after recovery is at least 70% of the original, and can even reach more than 85% of the original, or even more than 95%.

[0026] Furthermore, the self-assembling peptide hydrogel of the present invention still has the ability to self-repair after undergoing multiple shear thinning, that is, shear thinning can only temporarily destroy the three-dimensional network structure inside the peptide hydrogel, and has the potential to form gel in situ after injection. Shear thinning can be performed using a variety of mechanical forces that can apply shear or shear stress to the self-assembling peptide hydrogel, such as shaking, injection, etc., that is, after the microsphere filler is injected into the tissue, it can still be extracted by a syringe and then injected or shaken for further shaping changes.

[0027] The microsphere filler of the present invention can play a dispersing role without the assistance of other ingredients when used. After being injected into the tissue, it can self-assemble in response to proteins in the biological environment without introducing exogenous substances, thereby performing medical aesthetic regeneration and filling. At the same time, the microsphere filler of the present invention will not change the temperature and pH of the entire system during the self-assembly process and / or after forming a gel, which brings great safety guarantees for its clinical application in medical aesthetics.

[0028] The gel formed by the self-assembling peptide has a very large surface area, which allows nutrients, bioactive molecules and oxygen to diffuse fully. At the same time, the fibrous mesh scaffold material formed by the self-assembling peptide is similar to the extracellular matrix, providing a nanoscale microenvironment for cells, which is conducive to cell adhesion and growth. Therefore, while playing a filling role, the self-assembling peptide fully promotes the proliferation and differentiation of body cells in the self-assembling peptide material. During the degradation of the self-assembling peptide material, the body's cells continue to proliferate and differentiate in the self-assembling peptide scaffold, forming normally developed body tissues at the filling site. Even if the self-assembling peptide is completely degraded, the body tissue formed at the filling site still grows normally, achieving the effect of "permanent" filling and solving the problem that the filling effect disappears with the degradation of the filler material.

[0029] Compared with the mixed gel obtained by mixing hyaluronic acid and microspheres, there are occasional uneven dispersion and aggregation, which leads to injection difficulties and pain. The mixed gel obtained by using the self-assembling peptide of the present invention has a small molecular weight of the polypeptide and is assembled into nanofibers by non-covalent bonds. The microspheres in the system are individually wrapped by fine and dense polypeptide fibers, thereby fundamentally avoiding the phenomenon of aggregation between microspheres, which leads to injection difficulties and pain. At the same time, the use of self-assembling peptides as fillers eliminates the need for chemical modification of microspheres and various fillers, thereby reducing production costs.

[0030] During the injection of hyaluronic acid, if the injection volume is too large, large molecular hyaluronic acid is used, the doctor lacks skills, or the customer is not suitable for hyaluronic acid injection, it will cause agglomeration, facial stiffness, foreign body reaction, allergy and other unexpected situations. Self-assembling peptide hydrogel is formed by non-covalent bonds, and its relatively soft mechanical properties avoid the occurrence of agglomeration, stiffness, and foreign body reaction after injection. In addition, as an ideal tissue engineering scaffold material, self-assembling peptide hydrogel can provide a microenvironment close to the natural extracellular matrix for cell proliferation and differentiation. It has the characteristics of high purity, simple composition, degradability, no immune response, no animal-derived pollution, and the degradation products in the body are amino acids. It has been successfully used in the fields of cell engineering, tissue engineering, tissue repair and drug controlled release. Using self-assembling peptides as fillers can completely avoid the occurrence of allergic reactions.

[0031] Compared with ordinary hyaluronic acid fillers, which metabolize into CO2 and water in the body within 1 to 2 days, the cross-linking method (i.e., cross-linked hyaluronic acid) maintains the effect for about 6 to 9 months, and the efficacy of some products can be maintained for 1 to 2 years. In contrast, the hydrogel formed by self-assembling peptides has a very large surface area, which allows nutrients, bioactive molecules and oxygen to diffuse fully. At the same time, the fiber mesh scaffold material formed by the self-assembly of self-assembling peptides is similar to the extracellular matrix, providing a nano-scale microenvironment for cells, which is conducive to cell adhesion and growth. Therefore, while playing the role of filling, the self-assembling peptides fully promote the proliferation and differentiation of body cells in the self-assembling peptide material. During the degradation of the polypeptide material, the body's cells continue to proliferate and differentiate in the self-assembling polypeptide scaffold, forming normally developed body tissues at the filling site. Even if the self-assembling peptides are completely degraded, the body tissues formed at the filling site still grow normally, achieving the effect of "permanent" filling and solving the problem that the filling effect disappears with the degradation of the filler material. Therefore, the self-assembling peptide can play the role of uniformly dispersing PLLA microspheres in the composite preparation, and the hydrogel formed by its self-assembly can construct a regenerative environment in clinical applications, so that the microsphere filler can play a perfect regenerative filling role.

[0032] Glossary:

[0033] Hydrogel is a hydrophilic polymer material that can form a three-dimensional network structure by chemical or physical crosslinking. Hydrogel materials can come from natural and synthetic sources. Natural polymers such as chitosan, alginate, hyaluronic acid (HA), collagen, gelatin, etc. have the advantages of being biodegradable and carrying integrin binding sites, but they are immunogenic. Synthetic polymers such as polyethylene glycol (PEG), polyacrylamide (PAM), polyvinyl alcohol (PVA) and polymethyl methacrylate (PMMA) have the advantages of strong mechanical properties, customizability, and low immunogenicity, but lack innate biological functions and must undergo important post-processing to induce the desired response in vivo.

[0034] Hydrogels have the following properties:

[0035] 1. Good biocompatibility: The polymer contains a large number of hydrophilic groups, which can absorb dozens of times more water than itself, and has the characteristics of swelling but not dissolving in water, and has good water retention capacity;

[0036] 2. Similar to the extracellular matrix: Through structural design, the physical, chemical and mechanical properties of the hydrogel can be made similar to those of the extracellular matrix, which is conducive to cell growth and reproduction;

[0037] 3. Biodegradability: Some natural polymer materials are biodegradable, which can avoid secondary damage caused by implant removal. It is these unique advantages that make hydrogels shine in biomedical materials.

[0038] In the present invention, when a peptide having a structure having both a hydrophilic surface and a hydrophobic surface self-assembles under the conditions described in the present invention, especially physiological conditions, a hydrogel is obtained by encapsulating water.

[0039] Peptide Self Assembly is a short chain of amino acids with alternating charge domains and polar domains. When dissolved in neutral solvents and physiological salt concentrations, these peptides spontaneously assemble into hierarchical nanostructures through hydrogen bonds, ionic bonds, hydrophobic interactions or van der Waals forces. Materials derived from these components have the advantages of being non-toxic, non-immunogenic, non-thrombotic, degradable and easily metabolized. At the same time, nanofibers have the same size scale as natural ECM fibers, can be easily designed to simulate the stiffness of various soft tissues, and can be further functionalized by the attachment of cell-interacting peptide domains or cytokines and growth factors. Therefore, they can be used to design biologically relevant culture environments and improve the control of proliferating cell populations.

[0040] Self-assembling peptides can be used as hydrogels for wound treatment as drug carriers, and can also be used as peptide nanofibers for cancer treatment to continuously release small molecules, growth factors, and monoclonal antibodies. For example, self-assembling peptides can be used to promote angiogenesis in regenerated tissues and to repair skin wounds using peptide-based scaffolds. However, the field of injectable therapeutic hydrogels for self-assembling peptides is still in its infancy.

[0041] The alternating hydrophilic and hydrophobic amino acid residues in the self-assembling peptides enable the self-assembling peptides to retain a large amount of water to form a hydrogel. The side chains of the hydrophilic residues can directly interact with water, and the water molecules form inclusion complexes to surround the side chains of the hydrophobic residues. The number of hydrophobic residues and hydrophilic residues in the self-assembling peptides requires clever design and proportioning. If there are too many hydrophobic residues, the self-assembling peptides will be insoluble in water and precipitate out of the water; on the other hand, if there are too many hydrophilic residues, the self-assembling peptides are highly water-soluble and therefore cannot form a hydrogel. In addition, it is also necessary to precisely and cleverly induce the peptide molecules to self-assemble into ordered nanostructured materials, such as nanofibers, nanotubes, and nanovesicles.

[0042] "Amino acids" include those naturally occurring as well as non-naturally occurring amino acids, such as D-natural amino acids, beta and gamma derivatives. According to standard terminology, amino acid residue sequences may be named by three-letter or one-letter codes, for example: alanine (Ala, A); arginine (Arg,

[0043] R); Asparagine (Asp, N); Aspartic acid (Aspartic acid, D), Cysteine ​​(Cysteine, C); Glutamine (Glutamine,

[0044] Q); glutamic acid (Glu, E); glycine (G1y, G); histidine (His, H), isoleucine (Ile, I); leucine (Leu, L), lysine (Lys, L), methionine (Met, M); phenylalanine (Alanine, F); proline (Pro, P); serine (Ser, S); threonine (Thr, T); tryptophan (Trp, W), tyrosine (Tyr, Y); valine (Val, V); selenocysteine ​​(Sec, U); hydroxyproline (Hyp, O).

[0045] In the present invention, a "peptide" is an amino acid chain. In particular, a peptide is 2 to 40 amino acids in length.

[0046] In the present invention, "self-assembly" refers to the aggregation of polypeptides into an ordered structure under normal environmental conditions.

[0047] In addition, the preparation method of the obtained L-polylactic acid microspheres is simple, the conditions are mild, and the operation is easy. The raw material source is low-toxic or non-toxic, which is conducive to large-scale production and application.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] Compared with existing microsphere fillers, the fiber network formed by the self-assembling peptides in the present invention can wrap the microspheres and provide dispersion support for the microspheres, thereby fundamentally avoiding the phenomenon of microspheres agglomerating into lumps, which causes injection difficulties and pain.

[0050] The present invention uses self-assembling peptides as fillers, and does not require chemical modification of the microspheres, thereby reducing production costs and avoiding the occurrence of allergic reactions. The self-assembling peptides can achieve long-term and short-term therapeutic effects.

[0051] Compared with the existing preparation processes, the present invention uses a wide range of endogenous substances existing in the human body, such as serum, plasma, and animal and plant tissue fluids, as initiators, which reduces the safety risks in clinical applications and is particularly important for drug delivery, human tissue repair, and regenerative medicine. Description of the drawings:

[0052] Figure 1 Field emission scanning electron microscope image (FEI-Apreo) of the three-dimensional mesh scaffold material formed by the self-assembling peptides of the present invention: AF correspond to the self-assembling polypeptide SEQ ID 1-6 respectively.

[0053] Figure 2 The self-assembling peptide solution of the present invention can stably disperse L-polylactic acid microspheres: (A) scanning electron micrograph of L-polylactic acid microspheres, (B) particle size distribution of microspheres, (C) precipitation of microspheres in aqueous solution, (D) self-assembling peptide solution is a clear solution, (E) microspheres are uniformly suspended and dispersed in the self-assembling peptide solution; B shows that after the self-assembling peptide mixed solution of microspheres is mixed with tissue fluid, the self-assembling peptide L-polylactic acid microsphere solution quickly forms a hydrogel.

[0054] Figure 3 The process diagram of the self-assembling peptide of the present invention forming a hydrogel: (A) self-assembling peptide solution, (B) tissue fluid solution, (C) the response result of the self-assembling peptide solution and the tissue fluid, (D) the state of the self-assembling peptide at pH 9.4-9.6, (E) the state of the self-assembling peptide at neutral pH 7.2, (F) the self-assembling peptide can form a hydrogel and remains in a gel state after being squeezed out by a syringe.

[0055] Figure 4 This is a time scanning experimental result curve of the self-assembling peptide L-polylactic acid microspheres of the present invention.

[0056] Figure 5The infrared spectrum analysis diagrams of the self-assembling peptide of the present invention in the unexcited and excited states are as follows: (A) infrared spectrum of the unexcited self-assembling peptide, (B) second-order derivative of the corresponding spectrum of the unexcited self-assembling peptide, (C) secondary structure ratio of the unexcited self-assembling peptide system, (D) infrared spectrum of the excited self-assembling peptide, (E) second-order derivative of the corresponding spectrum of the excited self-assembling peptide, and (F) secondary structure ratio of the excited self-assembling peptide system.

[0057] Figure 6 In vitro degradation experiment of L-lactic acid microspheres: (A) Changes in surface morphology of microspheres under scanning electron microscope, (B) changes in lactic acid content of microspheres, (C) changes in pH of microspheres, and (D) changes in weight loss of microspheres. Specific implementation method:

[0058] The technical scheme of the present invention is further described below in conjunction with the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Given the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0059] Example 1. Synthesis of polypeptides (i.e., self-assembling peptides)

[0060] Six peptides were synthesized by a standard solid phase peptide synthesis method. The amino acid sequences are shown in Table 1 below. The amino acid sequences of the synthesized peptides were confirmed to be correct by high performance liquid chromatography and mass spectrometry.

[0061] Table 1. Peptide sequences

[0062]

[0063] Example 2. Preparation of polypeptide solution

[0064] Prepare 2% (w / v) polypeptide solution: add PBS buffer to appropriate amount of the powder of the self-assembling peptide of Seq1-4 obtained in Example 1 to obtain the mother solution of the self-assembling peptide shown in Seq1~4, and store it at 4°C for future use.

[0065] In addition, ultrapure water was added to an appropriate amount of the polypeptide powder of Seq 5-6 obtained in Example 1, and a small amount of sodium hydroxide solution was used to assist in the complete dissolution of the polypeptide. After dissolution, a trace amount of dilute hydrochloric acid and sodium hydroxide solution was used to adjust the pH of the solution to about 9.4-9.6 to obtain a 2% (w / v) self-assembling peptide mother solution and stored at 4°C for later use.

[0066] Example 3 Preparation of polypeptide three-dimensional mesh scaffold material

[0067] Experimental method: Use PBS buffer to dilute the peptide stock solution to obtain a 1% peptide solution of Seq 1 to 4; for Seq 5 to 6 peptides, use sodium hydroxide and hydrochloric acid to adjust the pH value of the peptide solution to 7.0 to 8.0, and use PBS or purified water to dilute to obtain a peptide solution with a final concentration of 1%.

[0068] In order to study the microscopic morphology of the final assembly of the peptide, the above samples were incubated in a 37°C oven for 30 minutes, first placed in a -80°C deep freezer to freeze it completely, then frozen in liquid nitrogen for 15 minutes, and freeze-dried in a vacuum freeze dryer. The surface morphology of the self-assembled peptide material was observed using a field emission scanning electron microscope (FEI-Apreo) at 1 kV. Before observation, gold was sprayed on the sample surface to increase the conductivity of the sample. The observation results are shown in Figure 1 As shown in A-1F.

[0069] Experimental results: After incubation in an oven, the peptide solutions of Seq 1 to 4 with a concentration of 1 wt % can form a relatively viscous liquid, while Seq 5 to 6 directly form a hydrogel with a solidified and stable shape.

[0070] After freeze-drying, the 1.0wt% self-assembling polypeptide hydrogel can be observed to form a highly interconnected, honeycomb-like pore structure. This phenomenon means that under neutral physiological conditions, the self-assembling polypeptide can self-assemble into a one-dimensional nanostructure and further form a three-dimensional network structure that mimics ECM.

[0071] Example 4: Dispersion and support functions of polypeptide three-dimensional mesh scaffold material on microspheres

[0072] Experimental method: Taking Seq 1 (IIIIIGSIIGPGGEGPGGV) as an example, the peptide solution prepared in Example 2 was diluted with physiological saline to prepare a peptide solution with a final concentration of 1 wt%. It was mixed with L-polylactic acid microspheres (particle size between 30-60 um, Figure 2 AB) to obtain a 5% self-assembling peptide mixed system of microspheres, which was compared with a L-polylactic acid microsphere group without adding self-assembling peptides and a single peptide group, and observed after standing for 72 hours.

[0073] Experimental results: The microspheres precipitated in the aqueous solution, and the microspheres were mainly concentrated at the bottom of the vial ( Figure 2 C), the self-assembling peptide solution is a clear solution ( Figure 2 D), after mixing the two, the microspheres are evenly and stably distributed in the self-assembling peptide solution, showing a three-dimensional and uniform distribution state. They are spread throughout the entire culture space. This uniform distribution pattern is achieved through non-stirring action ( Figure 2E). In medical aesthetic applications, the dispersion of functional microspheres has a great impact on their function. Areas where microspheres are too concentrated will excessively promote collagen proliferation and easily produce nodules; on the other hand, areas with low concentrations will have insufficient self-generated collagen, which will aggravate facial unevenness. The polypeptide / microsphere system formed by the present invention can completely avoid this problem.

[0074] In addition, except for Seq 1, the self-assembling peptides shown in Seq of the present invention can have the same function on a variety of other medical beauty regeneration microspheres (Table 2).

[0075] Table 2 Common medical microspheres:

[0076]

[0077] This experimental phenomenon proves that the hydrogel material of the present invention, that is, the three-dimensional network scaffold formed by peptide self-assembly, can effectively support medical beauty microspheres, and can play a good role in dispersing and supporting the microspheres when not activated; the entire experimental process does not require the addition of other ingredients, and the operation is convenient.

[0078] The results of the experiments of the self-assembling peptides shown by other sequence numbers are similar to those of this example and are not described in detail here.

[0079] Example 5 Experiment on the formation of injectable hydrogels from three-dimensional polypeptide scaffold materials

[0080] Experimental method: Taking Seq 2 (FLIVIGSIIGPGGDGPGGV) as an example, using the polypeptide solution prepared in Implementation Case 2, the obtained self-assembling peptide solution and human tissue fluid are evenly mixed in a volume ratio of 10:1 to obtain a self-assembled, three-dimensional network scaffold of adjustable self-assembling peptide hydrogel, and the pH value of the obtained mixed solution is neutral (about pH 6 to about pH 8). Figure 3 A. Figure 3 B. Figure 3 C are the appearance morphology of the peptide solution, human tissue fluid, and the combination of the peptide solution and human tissue fluid at room temperature. In addition, the study on short peptide Seq 6 (GIWLG) found that when the self-assembling peptide solution is at pH 9.4-9.6, the solution state is liquid ( Figure 3 D), and when the pH is adjusted to neutral 7.2, the system quickly becomes a hydrogel state ( Figure 3 E). The self-assembling peptide has a significant shear-thinning property, that is, it can be converted into a fluid state after being subjected to shear force, and it can be converted back into a gel state after being extruded and left to stand. Figure 3 The hydrogel in C was sucked through the syringe and squeezed out. Figure 3F, the hydrogel formed by the self-assembling peptide can be smoothly sucked by a syringe, and it is still in a gel state after being squeezed out by the syringe. This property gives the filler of the present invention great convenience in operation, and the mixed system can be easily distributed to the required position through a syringe, providing it with potential application value in the fields of cell culture, drug and cell delivery. Moreover, after pipetting or injection, the gel still has the same properties as the initial one.

[0081] Example 6 Strength determination of self-assembling peptide / microsphere composite gel system

[0082] Experimental method: Taking Seq 3 (FLIVIGSIIGPGGEGPGGV) as an example, according to the steps of implementation case 3, a solution with a final concentration of 1wt% of self-assembling peptides (sample A) was prepared; in addition, the obtained self-assembling peptide solution (sample A) was mixed with L-polylactic acid microspheres (particle size between 30-60um), and finally a self-assembling peptide mixed solution containing 5% microspheres (sample B) was obtained; the obtained self-assembling peptide solution (sample A) was mixed with human tissue fluid at a volume ratio of 10:1 to prepare a mixed solution containing a final concentration of 1wt% of self-assembling peptides (sample C); further, the C solution was mixed with L-polylactic acid microspheres (particle size between 30-60um), and finally a self-assembling peptide mixed solution containing 5% microspheres (sample D) was obtained. 200uL of each group of samples was added to the panel with a diameter of 20mm of the MARS60 rheometer, and the final modulus was recorded after a 30-minute time scan. The distance between the rotor and the panel is 500 mm, the shear strain is 1%, the frequency is 1 Hz, and the change degree of the storage modulus G' and the loss modulus G" and the gelation time of the response are detected. The whole test is completed at 37 ° C. Corresponding to the sample number, the results are shown in Figure 4 A, B, C, D.

[0083] Experimental results: The peptide itself was in a solution state. After the addition of the stimulating substance, it quickly formed a gel. The hydrogel stimulated by the tissue fluid formed a gel within 30 minutes and remained stable thereafter. In each sample with a self-assembling peptide concentration of 1wt%, when the self-assembling peptide existed alone and when only microspheres were added ( Figure 4 A, and Figure 4 B), although its storage modulus is higher than the loss modulus, there is no significant difference, and both are lower than 2Pa, and the macroscopic appearance is liquid rather than solid; when tissue fluid and microspheres exist in the sample ( Figure 4 C, and Figure 4D), the storage modulus (G') of the mixed system of the present invention rises rapidly within 5 minutes, which is significantly higher than the loss modulus (G"), and a high-strength hydrogel with an elastic modulus greater than 300Pa is formed within 30 minutes, and the elastic modulus of the sample containing both microspheres and tissue fluid is as high as 600Pa. This shows that the self-assembling peptide microsphere system of the present invention rapidly assembles to form a stronger and more stable gelation state, and has a stronger supporting effect.

[0084] Example 7 Infrared analysis of the structure of three-dimensional polypeptide mesh scaffold material

[0085] Experimental method: This experiment takes Seq 4 (FLIVIGSIIGPGGDGPGGD) as an example. Ultrapure water is used to dissolve the assembled peptide freeze-dried powder, and tissue fluid is added at a volume ratio of 10:1 and mixed evenly to obtain a mixed system with a final concentration of self-assembling peptide of 1wt%. In addition, a 1.0wt% polypeptide solution was used as a control group. The above samples were incubated in a 37°C oven for 30 minutes, first placed in a -80°C deep-freezer to freeze them thoroughly, and then frozen in liquid nitrogen for 15 minutes and placed in a freeze dryer for freeze drying. The sample was prepared by the potassium bromide tablet method, and the infrared scanning was performed using the Nicolet iS5 infrared instrument with a wavenumber scanning range of 1750-1450cm -1 The wave number resolution is 0.5 cm -1 The infrared data of each group were normalized using Origin.

[0086] Experimental results: The infrared spectra of excited and unexcited peptide solutions were obtained ( Figure 5 AD), further observe the second-order derivative spectrum ( Figure 5 BE), the characteristic peaks related to α-helix, β-fold, β-turn and random coil can be clearly distinguished. Figure 5 C), in the secondary structure formed by peptide self-assembly, α-helix accounts for 28.9%, β-fold accounts for 19%, β-turn accounts for 22%, and random coil accounts for 30.1%; the excited group ( Figure 5 F), the proportion of α-helix increased significantly to 50.5%, β-fold accounted for 17.3%, β-turn accounted for 24%, and random coil decreased to 8.2%.

[0087] The results show that the β-fold and β-turn structures do not change much during the assembly process, and a large number of random coils are converted into α-helical structures during the assembly process. During the assembly of polypeptides, various secondary structures will be generated. These secondary structures have an important influence on the self-assembly behavior, stability and biological activity of polypeptides. α-helix is ​​a stable conformation of polypeptide chains, and the increase of α-helical structure means that the polypeptide chain is more stable.

[0088] Because the nanofibers aggregate and self-assemble through non-covalent interactions, they connect to form a sheet structure, which is more stable. The resulting porous structure is suitable for cell growth and can realize the transportation of nutrients and oxygen.

[0089] Example 8 Determination of in vitro degradation of L-polylactic acid microspheres

[0090] It takes about 6 to 18 months for the L-polylactic acid microspheres used for regenerative medical aesthetic materials to be completely absorbed in the human body, so that they can effectively achieve the effect of continuous induction of collagen regeneration. The slow and continuous release of macromolecules from L-polylactic acid microspheres mainly depends on the long-term degradation process of L-polylactic acid, so it is necessary to study the degradation law and mechanism of polylactic acid.

[0091] Experiment 1: Changes in microsphere surface morphology

[0092] Experimental method: blank microspheres (70 mg) were suspended in 12 ml of degradation medium, which was phosphate buffer (pH 7.4). The sample was oscillated on a 37°C constant temperature table oscillator at a speed of 50 r / min. -1 . 20 samples were subjected to degradation test at the same time. One sample was taken out every five days, and the rest of the samples continued to degrade. The solid part of the taken out samples was collected, and the changes in the morphology and size of the microspheres were observed using a scanning electron microscope.

[0093] Experimental results: Before degradation, the microsphere surface is smooth and has no holes. After degradation, the microsphere surface is perforated. Further degradation forms an uneven surface with grooves and ridges of different depths. As degradation continues, the various parts of the microsphere gradually dissolve and the microsphere becomes coral-like. The PLA microspheres with smaller molecular weight degrade faster, while the PLA microspheres with larger molecular weight degrade slower. Figure 6 A) Combined with the above, the process of morphological changes of microspheres during degradation can be observed.

[0094] Experiment 2: Determination of lactic acid content

[0095] Experimental method: blank microspheres (70 mg) were suspended in 12 ml of degradation medium, which was phosphate buffer (pH 7.4). The sample was oscillated on a 37°C constant temperature table oscillator at a speed of 50 r / min. -1. 20 samples were subjected to degradation test at the same time. One sample was taken out every five days, and the rest of the samples continued to degrade. The liquid part of the taken samples was collected, and PBS (pH7.4) was used as blank to measure the absorbance of the liquid part at a wavelength of 270nm. At the same time, deionized water was prepared as a control solution to measure the absorbance. The lactic acid concentration of the liquid part was calculated by the reference substance comparison method according to the following formula: Ci = (A / iAr) Cr, where Ci is the concentration of the test solution; Ai is the absorbance of the test solution; Cr is the concentration of the reference solution; Ar is the absorbance of the reference solution.

[0096] Experimental results: Polylactic acid degrades to generate lactic acid, which participates in sugar metabolism in vivo and further degrades to generate CO2 and water in vitro. The lactic acid content in the medium of the in vitro degradation system gradually increases, and the degradation rate of microspheres slows down with the increase of relative molecular mass, which is manifested as slow lactic acid generation. Polylactic acid has a large relative molecular mass and contains a large number of lactic acid monomers, so the lactic acid peak concentration is high ( Figure 6 B). The degradation time of poly(L-lactic acid) microspheres in the human body is closely related to the molecular weight of the microspheres. Low molecular weight microspheres are completely degraded faster in the human body.

[0097] Experiment 3: Determination of polymer mass reduction

[0098] Experimental method: blank microspheres (70 mg) were suspended in 12 ml of degradation medium, which was phosphate buffer (pH 7.4). The sample was oscillated on a 37°C constant temperature table oscillator at a speed of 50 r / min. -1 . 20 samples were subjected to degradation test at the same time. One sample was taken out every five days, and the rest of the samples continued to degrade. The solid part of the taken out samples was collected. The solid part was first accurately collected by microporous filter membrane and vacuum dried. The microspheres were fully dried to constant weight and accurately weighed. The weight of the microspheres before degradation is Wi. The weight of the microspheres after degradation is Wr. The weight loss percentage = [(Wi-Wr) / Wi]×100%.

[0099] Experimental results: During the degradation process, the mass of the polymer microspheres continued to decrease, which can be divided into two stages: Figure 6 C) The mass of the microspheres remained basically unchanged or decreased slowly in the first stage, and decreased significantly in the second stage. In general, the larger the relative molecular mass of polylactic acid, the slower the mass reduction rate and the slower the degradation.

[0100] Experiment 4: Determination of pH

[0101] Experimental method: blank microspheres (70 mg) were suspended in 12 ml of degradation medium, which was phosphate buffer (pH 7.4). The sample was oscillated on a 37°C constant temperature table oscillator at a speed of 50 r / min. -1. 20 samples were subjected to degradation test at the same time. One sample was taken out every five days, and the rest of the samples continued to degrade. The liquid part of the taken samples was collected, and the pH of the liquid part was measured using a pH meter.

[0102] Experimental results: Polylactic acid degrades to generate acidic groups, which lowers the pH of the medium and accelerates the degradation rate of the microspheres. Polylactic acid has a small relative molecular mass and the degree of pH reduction is significant, indicating that the degradation rate of the polymer slows down with the increase of relative molecular mass ( Figure 6 D).

[0103] Combined with experiments 1 to 4, in the early stage of degradation, the mass and morphology of the polymer rarely change, and the degradation mainly occurs in the breakage of the molecular chain; when the degradation reaches a certain extent, the mass and morphology of the polymer change significantly, the degradation process automatically accelerates, and the microspheres dissolve quickly until they disappear completely. The degradation rate of polylactic acid slows down with the increase of the average relative molecular mass, so the drug release rate in the microspheres also slows down with the increase of the relative molecular mass of polylactic acid.

[0104] With the above ideal examples of the present invention as inspiration, through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A microsphere filler comprising a self-assembling polypeptide compound and microspheres; characterized in that: The polypeptide compound can form nano-scale fibers in a solution without chemical modification and present a three-dimensional network structure; and the three-dimensional network structure can support the microspheres in the solution so that they are evenly dispersed and three-dimensionally distributed.

2. The microsphere filler according to claim 1, characterized in that: The polypeptide compound is selected from the following polypeptides: SEQ ID 1, IIIIIGSIIGPGGEGPGGV SEQ ID 2, FLIVIGSIIGPGGDGPGGV SEQ ID 3, FLIVIGSIIGPGGEGPGGV SEQ ID 4, FLIVIGSIIGPGGDGPGGD SEQ ID 5, GIIIG SEQ ID 6, GIWLG.

3. The microsphere filler according to claim 1, characterized in that The microspheres are not chemically modified; preferably, the microspheres are selected from at least one of L-polylactic acid microspheres, polycaprolactone microspheres, polylactic acid-glycolic acid microspheres, hydroxyapatite microspheres, polymethyl methacrylate microspheres and polyvinyl alcohol microspheres.

4. The microsphere filler according to any one of claims 1 to 3, characterized in that: The particle size of the microspheres is 3-150 μm; Preferably, the particle size of polylactic acid microspheres is 10-60 μm, the particle size of polycaprolactone microspheres is 10-60 μm, the particle size of polylactic acid-glycolic acid microspheres is 20-60 μm, the particle size of hydroxyapatite microspheres is 25-45 μm, and the particle size of polymethyl methacrylate microspheres is 20-60 μm.

5. A preparation comprising the microsphere filler according to any one of claims 1 to 4, characterized in that: The preparation is a solution preparation, a freeze-dried powder preparation, or a suspension preparation.

6. The preparation of microsphere filler according to claim 5, characterized in that: The solution in the solution preparation or suspension is water, or physiological saline, or phosphate buffer.

7. The preparation of microsphere filler according to claim 6, characterized in that: In the solution preparation, the concentration of microspheres is controlled at 1wt%-40wt%; the concentration of the polypeptide is controlled at 0.05%-3%.

8. Use of the microsphere filler according to any one of claims 1 to 4 or the microsphere filled preparation according to claim 5, characterized in that: The microsphere filler or microsphere filling auxiliary is used in regenerative medicine and tissue regeneration; drug delivery; wound healing; implantable materials; gene therapy; stem cell therapy; and medical cosmetology.

9. The use according to claim 7, characterized in that: When using the microsphere filler or microsphere-filled preparation, first add injection water, physiological saline or phosphate buffer solution to the freeze-dried polypeptide powder and mix them evenly. The dissolved polypeptide self-assembles to form a three-dimensional network structure under the action of non-covalent bonds. The network structure formed by the self-assembled polypeptide supports the medical beauty microspheres in a liquid state, so that the medical beauty microspheres are evenly three-dimensionally distributed in the polypeptide self-assembled network material, and a uniformly dispersed medical beauty microsphere filler that can be injected and filled can be quickly obtained.

Citation Information

Patent Citations

  • High-dispersity injectable poly-L-lactic acid microspheres and preparation method thereof

    CN117618650A